GSK3β-dependent lysosome biogenesis: An effective pathway to mitigate renal fibrosis with LM49 - Ren, Jinhong; Wei, Huizhi; Sun, Jian; Feng, Xiue; Zhang, Yuanlin; Yuan, Hongxia; Miao, Junqiu; Qi, Xiaoming; Qiao, Yuanbiao; Xiao, Baoguo; Li, Qingshan (Frontiers in Pharmacology, 2022)
Renal fibrosis is an incurable disorder characterised by an imbalance of the extracellular matrix (ECM) favouring excess production over degradation. The identification of actionable pathways and agents that promote ECM degradation to restore ECM homeostasis may help mitigate renal fibrosis. In this study, we identified 5,2′-dibromo-2,4′,5′-trihydroxydiphenylmethanone (LM49), a compound we previously synthesised, as a small-molecule inducer of ECM degradation. LM49 administration efficiently reduced ECM deposition in renal tissue of diabetic nephropathy rats and in transforming growth factor β-treated renal fibroblast cells. LM49 promoted the cytosol-to-nucleus translocation of transcription factor EB (TFEB) to increase lysosome biogenesis, leading to lysosome-based degradation of the ECM. TFEB-mediated lysosome biogenesis was induced by LM49 directly inhibiting the activity of glycogen synthase kinase 3β (GSK3β) rather than mammalian target of rapamycin complex 1. LM49 inhibited GSK3β kinase activity concentration-dependently via competing with ATP. Direct binding between LM49 and GSK3β was confirmed by the bio-layer interferometry assay, cellular thermal shift assay, and drug affinity responsive target stability. A molecular docking and molecular dynamic simulation revealed that LM49 occupied the ATP pocket of GSK3β, which was consistent with the kinase activity assay. In summary, LM49 enhances TFEB-mediated lysosome biogenesis by directly inhibiting GSK3β, leading to the degradation of the ECM by lysosomes. The enhancement of GSK3β-dependent lysosome biogenesis to rebalance the ECM may be a novel strategy to counteract renal fibrosis, and LM49 may be a viable clinical candidate for treating this disorder.